Aberrant nuptials Deleuze and artistic research 2 - Assis, Paulo de 1969-; Giudici, Paolo (Leuven University Press, 2019)
Aberrant Nuptials' explores the diversity and richness of the interactions between artistic research and Deleuze studies. 'Aberrant nuptials' is the expression Gilles Deleuze uses to refer to productive encounters between systems characterised by fundamental difference. More than imitation, representation, or reproduction, these encounters foster creative flows of energy, generating new material configurations and intensive experiences. Within different understandings of artistic research, the contributors to this book - architects, composers, film-makers, painters, performers, philosophers, sculptors, and writers - map current practices at the intersection between music, art, and philosophy, contributing to an expansion of horizons and methodologies. Written by established Deleuze scholars who have been working on interferences between art and philosophy, and by musicians and artists who have been reflecting Deleuzian and Post-Deleuzian discourses in their artworks, this volume reflects the current relevance of artistic research and Deleuze studies for the arts.
Introduction: "Aberrant Nuptials: Deleuze and Artistic Research 2" brings together a collection of essays originating from the second international conference on Deleuze and Artistic Research (DARE), held at the Orpheus Institute, Ghent, 20-22 November 2017 (Seite 9)
Keywords: Deleuze, Gilles -- 1925-1995; Künste; Ästhetik; Deleuze, Gilles,-1925-1995-Congresses; Arts / Research; Arts / Philosophy; Deleuze, Gilles / 1925-1995 / Influence; Deleuze, Gilles / 1925-1995; Influence (Literary, artistic, etc.); Konferenzschrift -- 20.11.2017-22.11.2017 -- Gent